Exploring the counseling experiences of Filipino counselors with lesbians, gays and bisexuals - Pantaleon, Jaymee Abigail K. (Animo Repository, 2009)
This study aims to explore the Counseling Experiences of Filipino Counselors with Lesbians, Gays and Bisexuals. It specifically seeks to answer the following questions: Significant Counseling Experiences of Filipino Counselors with Lesbians, Gays and Bisexuals and the Counselors thoughts and feelings in the beginning and end phase of counseling LGB clients. Twelve Filipino Counselors who are currently practicing counseling in the Philippines are the participants of this study. They include psychologists, clinicians, and counselors working in a community, clinical or educational setting. Each of them had at least one counseling experience with an LGB client. A qualitative descriptive research design using an in-depth interview guide was employed in this study. Through this research method, this study takes into account that viewpoints and practices in the field are different because of the diverse subjective perspectives and social background related to them. The findings in this study reveal that the counselors beliefs, values and attitudes play an important role in the counseling process and outcome. Furthermore, counselors are accepting of their LGB client and sensitive to their concerns. Despite their own personal beliefs and biases, they still accepted their LGB clients in counseling because it is their call of duty. Based on their perceived need, it is recommended that the counselor should be aware of his own biases and prejudices towards LGB clients. This awareness would aid the counselor in helping the client more effectively. Continuing professional growth such as attending seminars and LGB forums, reading journals, doing research and enrolling into graduate studies would also help in counseling LGB clients better.